Audio –Visual Input for Improving the Cognitive Skills of Grade 10 Students in Araling Panlipunan - Privado, Norielyn R.; Hermosa, Jherwin F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to improve the cognitive competence of the students by utilizing audio-visual inputs. The study employed the one-group-pretest-posttest research design under a pre-experimental study participated by 34 Grade Ten (10) respondents in San Isidro National High School who were chosen using the cluster sampling technique. This study utilized a one-group-pretest-posttest research design under a pre-experimental study. Data were gathered using pre-test and post-test questionnaires validated by the experts. Standard deviation and weighted mean were used to analyze the pre-test and post-test scores. T-test was used to calculate the significant difference. The study’s findings revealed a significant difference between the pre-test and post-test scores. Specifically, perception has a .008 significant difference, attention with a .006 significant difference, memory with a .005 significant difference, and logical reasoning with a .007 considerable difference.